(untitled) (Journal of Laboratory Animal Science, 2023)
The preferred site for blood collection for clinical pathology assessment depends on the volume and type of blood required, sampling intervals and state of consciousness of animals during sampling. Blood sampling from jugular vein from conscious rats has multiple advantages including simplicity, speed, the ability to incorporate repeated sampling (decreasing the need for satellite groups), collection in conscious animals and supports three Rs (Replacement, Reduction and Refinement). The objectives of this study were to standardise single handed jugular vein sampling in conscious male rats and compare the clinical pathology data generated, with samples obtained from fasted and anesthetized rats via retro-orbital bleeding, abdominal aorta and heart (ventricles). Forty-eight (48) rats were grouped into twelve rats each, per group per route. No biological or statistically significant differences were observed in any of clinical pathology parameters obtained by jugular vein blood collection in conscious rats compared to blood samples collected from other sampling routes under isoflurane anesthesia. It is concluded that single-handed blood sampling from jugular veins of conscious male Sprague-Dawley rats resulted in acceptable quality of samples for clinical pathology assessment. The single-handed jugular vein sampling technique can be considered as advantageous on welfare grounds as rats can be returned to the cages within minutes after sampling, consequently reducing the stress. Additionally, blood sampling from conscious rats enable the interpretation of the clinical pathology data without being influenced by anesthesia.